Study on Fracture Distribution and Local Brittleness Characteristics Based on Stepwise Regression Method. (29th August 2021) - Zhao, Wanchun; Feng, Xiaohan; Wang, Tingting
Abstract : The brittleness of rock is an important parameter that influences and controls the evolution mechanism of the fracture and formation of a fracture net. The existing methods of brittle characterization are describing the brittleness of rock mass as a whole. They lack reliability descriptions to guide the fracture strike and improve the volume of the reservoir. It is considered that the macroscopic brittle fracture of a rock is the process of continuous initiation and propagation of local fractures in the rock mass under the action of external loads. The macroscopic fracture is the appearance caused by a local rupture to a certain extent, and the local rupture is the root cause of macroscopic fracture. The study of the local brittleness of a rock can reveal the intrinsic nature of its fracture behavior and can reflect the evolution mechanism of fracture more directly and accurately. In this paper, coring sampling in field outcrop is first carried out, and the break evolution law of core is described by a CT scanner. The mineral compositions in the core are determined by a mineral analysis diffractometer. The regulation of the rock local brittleness with different mineral contents is analyzed. And a new method for local brittle region division and characterization of rock has been developed. This method gives the connotation relation of the rock brittle fracture as a whole induced by a local brittle fracture. And it provides a new approach to study the law of a rock fracture.